Significant associations between C-reactive protein levels, body adiposity distribution and peripheral blood cells in schoolage children - Salgado-Bernabé, Aralia Berenice; Ramos-Arellano, Luz Elena; Guzmán-Guzmán, Iris Paola; Muñoz-Valle, José Francisco; Castro-Alarcón, Natividad; Vences-Velázquez, Amalia; Salgado-Goytia, Lorenzo; Parra-Rojas, Isela (Investigación Clínica, 2016)
Obesity is associated with a state of chronic low-grade inflammation. Generally, there are significant correlations between body mass index and increased C-reactive protein levels. We investigated the relationship of high sensitivity C-reactive protein (hsCRP) levels with body adiposity distribution and blood cell count in obese children. A cross-sectional study was performed in 225 Mexican children. In the study were included 106 obese and 119 normal-weight children, aged 6-13 years old. The body composition was evaluated by BMI, body circumferences and skinfold thickness. hsCRP levels and hematological parameters were analyzed in all children. The hsCRP levels were higher in obese children than in the control group (1.5 and 0.41 mg/L respectively, P<0.001). Interestingly, hsCRP levels >3 mg/L were associated with the increase of circumferences of the waist, hip and arms (ORs=9.08, 6.78 and 8.73, respectively, P<0.001), and a higher thickness of triceps, subscapular and suprailiac skinfolds (ORs= 4.73, 6.39 and 5.26, respectively, P=0.001), as well as a higher leukocyte and platelet counts. The data suggest that hsCRP levels are associated with skinfold thickness and body circumferences, and a moderate relationship was found with leukocyte and platelet counts in the studied children